Highly Stable Sr-Free Cobaltite-Based Perovskite Cathodes Directly Assembled on a Barrier-Layer-Free Y2O3-ZrO2 Electrolyte of Solid Oxide Fuel Cells - Ai, Na; Li, N.; Rickard, William; Cheng, Yi; Chen, Kongfa; Jiang, San Ping (Wiley-VCH Verlag GmbH, 2017)
Direct assembly is a newly developed technique in which a cobaltite-based perovskite (CBP) cathode can be directly applied to a barrier-layer-free Y2O3-ZrO2 (YSZ) electrolyte with no high-temperature pre-sintering steps. Solid oxide fuel cells (SOFCs) based on directly assembled CBPs such as La0.6Sr0.4Co0.2Fe0.8O3-d show high performance initially but degrade rapidly under SOFC operation conditions at 750 °C owing to Sr segregation and accumulation at the electrode/electrolyte interface. Herein, the performance and interface of Sr-free CBPs such as LaCoO3-d (LC) and Sm0.95CoO3-d (SmC) and their composite cathodes directly assembled on YSZ electrolyte was studied systematically. The LC electrode underwent performance degradation, most likely owing to cation demixing and accumulation of La on the YSZ electrolyte under polarization at 500 mA cm-2 and 750 °C. However, the performance and stability of LC electrodes could be substantially enhanced by the formation of LC-gadolinium-doped ceria (GDC) composite cathodes. Replacement of La by Sm increased the cell stability, and doping of 5 % Pd to form Sm0.95Co0.95Pd0.05O3-d (SmCPd) significantly improved the electrode activity. An anode-supported YSZ-electrolyte cell with a directly assembled SmCPd-GDC composite electrode exhibited a peak power density of 1.4 W cm-2 at 750 °C, and an excellent stability at 750 °C for over 240 h. The higher stability of SmC as compared to that of LC is most likely a result of the lower reactivity of SmC with YSZ. This study demonstrates the new opportunities in the design and development of intermediate-temperature SOFCs based on the directly assembled high-performance and durable Sr-free CBP cathodes.